Milk Production -Forecasting In Khartoum State, Sudan - Hassan, Safa Abdelgadier; Abdelaziz, Hag Hamad; Ibrahim, Abdelateif Hassan; Musa, Khalid Salih Mohamed (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The objective of this study was forecast milk production of Khartoum State, during (2018-2030), different techniques used for the prediction of total year milk yield. Auto-Regressive Integrated Moving Average (ARIMA) Model with statistical time –series modeling technique was used to develop using 29 yr. of historical milk-production data. The models predicted the total annual milk production, as performance measures, ARIMA analysis of the Mean Absolute Percentage Error (MAPE) was found to be 1.611. So, the ARIMA (1.0.0) model obtained accurate results regarding the performance to forecasting the dairy production.